Robust and Quality Boundary Constrained Tetrahedral Mesh Generation (Communications in Computational Physics, 2013)
A novel method for boundary constrained tetrahedral mesh generation isproposed based on Advancing Front Technique (AFT) and conforming Delaunay triangulation. Given a triangulated surface mesh, AFT is firstly applied to mesh severallayers of elements adjacent to the boundary. The rest of the domain is then meshedby the conforming Delaunay triangulation. The non-conformal interface between twoparts of meshes is adjusted. Mesh refinement and mesh optimization are then preformed to obtain a more reasonable-sized mesh with better quality. Robustness andquality of the proposed method is shown. Convergence proof of each stage as well asthe whole algorithm is provided. Various numerical examples are included as well asthe quality of the meshes.